Development of polyurethane foam dressing containing silver and asiaticoside for healing of dermal wound - Nantaporn Namviriyachote; Vimolmas Lipipun; Yada Akkhawattanangkul; Phingphol Charoonrut; Garnpimol C. Ritthidej (Elsevier, 2019)
Polyurethane foam dressings for dermal wounds were formulated with natural polyols in order to improve the foam characteristics and the release of 2 active agents, silver and asiaticoside (AS) as an antimicrobial agent and an herbal wound healing agent, respectively. The foam was instantly formed by interaction of polyols and diisocyanate. Hydroxypropyl methylcellulose, chitosan and sodium alginate were individually mixed with the main polyols, polypropylene glycol, in the formulation while the active components were impregnated into the obtained foam dressing sheets. Although the type and amount of the natural polyols slightly affected the pore size, water sorption-desorption profile and compression strength of the obtained foam sheets, a prominent effect was found in the release of both active components. Among natural polyols formulations, foam sheets with alginate showed the highest silver and AS release. Non-cytotoxicity of these foam sheets to human fibroblast cells was confirmed. Antimicrobial testing on four bacteria strains showed that 1 mg/cm2 silver in formulations with 6% of natural polyols and without natural polyols had sufficient content of the silver release with comparable inhibition zone and significantly larger zone than other formulations. In pig study, the foam dressing with 6% alginate, 1 mg/cm2 silver and 5% AS could improve wound healing in both the percentage of the wound closure and histological parameters of the dermal wound without any dermatologic reactions. In conclusion, this innovative foam dressing had potential to be a good candidate for wound treatment. Keywords: Polyurethane foam dressing, Natural polyols, Silver nanoparticles, Asiaticoside, Wound healing